INTEGRASI ALQURAN DAN SAINS: SUATU PERSPEKTIF KOMUNIKASI - Muhammad Anshar Akil (Jurnal Dakwah Tabligh, 2017)
Al-Quran have a great attention to science and provide a high status on people who mastering science. One of the fields of science be the object of Al-Quran is communication. The scope and functions of communication studies in the Quran (Islamic communication) a wider than science of communication. To develop the science of communication in harmony with the values of revelation, it is important to study communication refers to the principles of communication in the Quran. Duty of Muslims to integrate into the Quranic values in modern science so that the communication of science is not only based on the paradigm of modern science, but also contains the values of Divinity. Communication science which only talking about inter-human communication can be adopted into Islamic communication as long as not contrary to Islamic values. Instead, science communication learned during these can be enriched by Islamic principles of communication.